Framework for the evaluation of an information system. (19th April 2004) - Irani, Z.
Manufacturing Resource Planning (MRPII) systems offer many organisations the opportunity to reap a wide variety of strategic and operational benefits. However, even though many of these benefits are suitable for evaluation within traditional accountancy frameworks, it is the intangible and non-financial benefits, together with the indirect project costs, which complicate the justification of Information Technology (IT) and Information Systems (IS). As a result, many companies are finding themselves unable to assess the "full" implications of their MRPII investments, thus amounting to an appraisal process limited to the benefits and costs financially quantifiable. This therefore questions the predictive value of those justification processes that make use of traditional appraisal techniques. As a result, many companies are forced to adopt one of the following strategies: (i) a refusal to undertake IT/IS projects whose benefits and costs are not financially quantifiable; (ii) invest in IT/IS projects as an "act of faith"; or, (iii) use "creative" accounting as a method of passing the budgetary process. This paper reviews the published literature and offers a taxonomy of investment appraisal techniques, together with their inherent limitations when used as part of an MRPII justification process. The author then presents a conceptual framework for the evaluation of IT/IS investments in manufacturing, with a particular focus on MRPII. The proposed framework: (i) distinguishes the different types of justification processes necessary; (ii) accounts for the selection of the most appropriate technical specification and supplier(s); (iii) identifies human and organisational issues; (iv) acknowledges the limitations inherent in traditional appraisal techniques; (v) suitably places the implementation process within project evaluation; and (vi) integrates a feedback mechanism to ensure that when the system has been implemented, a management review assesses whether the planned project objectives have been realised. Finally, the paper concludes with those implications associated with the development of a descriptive MRPII evaluation framework.